2023
DOI: 10.13075/ijomeh.1896.02114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of health behaviours of Polish Army soldiers in relation to demographic factors, body weight and type of Armed Forces

Abstract: The aim of this article is to assess the health behaviors of Polish Army soldiers participating in the National Health Programme 2016-2020 in relation to types of armed forces, BMI and selected demographic factors. Material and Methods: Anthropometric and questionnaire data were obtained in a group of 1229 soldiers of the Polish Armed Forces (PAF) from military units from all over Poland. Health behaviors patterns were assessed using the Health Behavior Inventory (HBI), developed by Juczyński. Results: The HBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…If preventive measures for obesity, lifestyle and physical fitness are not implemented there would be a large economic burden related to the cost of treatment for the resulting medical conditions [ 27 ]. Gazdzinska et al studied the health behavior of Polish soldiers and found that normal-weight soldiers with higher education living in big cities showed significantly stronger health behavior than soldiers with lower education living in rural areas who were diagnosed with obesity [ 35 ]. The authors recommend increased education on health-promoting behaviors and organized training with psycho-dietary counselling for obese soldiers [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…If preventive measures for obesity, lifestyle and physical fitness are not implemented there would be a large economic burden related to the cost of treatment for the resulting medical conditions [ 27 ]. Gazdzinska et al studied the health behavior of Polish soldiers and found that normal-weight soldiers with higher education living in big cities showed significantly stronger health behavior than soldiers with lower education living in rural areas who were diagnosed with obesity [ 35 ]. The authors recommend increased education on health-promoting behaviors and organized training with psycho-dietary counselling for obese soldiers [ 35 ].…”
Section: Discussionmentioning
confidence: 99%